Group I metabotropic glutamate receptor plasticity after peripheral inflammation alters nociceptive transmission in the dorsal horn of the spinal cord in adult rats. Issue 1 (October 2017) - Radwani, Houda; Roca-Lapirot, Olivier; Aby, Franck; Lopez-Gonzalez, Maria Jose; Bouali-Benazzouz, Rabia; Favereaux, Alexandre; Errami, Mohammed; Landry, Marc; Fossat, Pascal
The dorsal horn of the spinal cord is a crucial site for pain transmission and modulation. Dorsal horn neurons of the spinal cord express group I metabotropic glutamate receptors (group I mGluRs) that exert a complex role in nociceptive transmission. In particular, group I mGluRs promote the activation of L-type calcium channels, voltage-gated channels involved in short- and long-term sensitization to pain. In this study, we analyzed the role of group I mGluRs in spinal nociceptive transmission and the possible cooperation between these receptors and L-type calcium channels in the pathophysiology of pain transmission in the dorsal horn of the spinal cord. We demonstrate that the activation of group I mGluRs induces allodynia and L-type calcium channel-dependent increase in nociceptive field potentials following sciatic nerve stimulation. Surprisingly, in a model of persistent inflammation induced by complete Freund's adjuvant, the activation of group I mGluRs induced an analgesia and a decrease in nociceptive field potentials. Among the group I mGluRs, mGluR1 promotes the activation of L-type calcium channels and increased nociceptive transmission while mGluR5 induces the opposite through the inhibitory network. These results suggest a functional switch exists in pathological conditions that can change the action of group I mGluR agonists into possible analgesic molecules, thereby suggesting new therapeutic perspectives to treat persistent pain in inflammatory settings.